An Integrated Approach to Mark-Lip Determination for Large Building Contractors in Ghana (Journal of Science and Technology, 2016)
Most clients in Ghana use the competitive bidding system to select a suitable contractor to execute a building project The hid price, submitted by contractors, comprises an estimate of the direct cost, indirect cost and a mark-up The mark-up is a percentage of the estimated total cost, which a contractor adds to the estimated direct and indirect costs to account for head office overhead coot, profit and contingencies. The site of the mark-up for a contractor varies from one bid to another, depending on a multiplicity of internal and external factor. that are encountered in each markup decision. The very existence of a construction firm depends on its ability to assign an appropriate markup, which will enable the company to get enough jobs and significant profits. Therefore, it is a must that each contractor develops an integrated approach for determining this ninth-up, which allows the company to achieve in objectives under different bidding situations This paper first identifies the MOM important factors affecting the determination of the markup and further highlights the use of the selected factors to establish a fair and reasonable mark-up that satisfies the required rate of return of the contractor from the particular (or at least the general risk-class of) project at hand The approach developed will provide an analytical tool for establishing optimum mark-up for construction projects in Ghana.